Effect of molecular structure on oxidative degradation of polyol ester - Abdul Raof, Nurliyana; Yunus, Robiah; Rashid, Umer; Azis, Norhafiz (Malaysian Tribology Society, 2018)
An experimental investigation was conducted to explore the thermal and heat flow characteristics of polyol esters with different molecular structures by using simultaneous thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) measurement. A significant difference in onset temperature between the developed esters and mineral oil was observed. The comparison of oxidative stability of polyol esters and mineral transformer oil revealed that polyol esters are oxidatively stable up to >370°C while for mineral oil it was <300°C. As oxidative degradation starts at a lower temperature than thermal degradation, determination of oxidative stability is more important to study the potential the ester to be used as dielectric fluid.